Factors Influencing Adaptation of Indonesian Graduate Students in Universiti Putra Malaysia - Hayani (2004)
One of the focuses in implementing the Second Long-term Development Program (1993-2018) in Indonesia is to enhance human resource development. It is directed to obtain high quality human resources through increasing their skills and technology, which in turn can be applied for the need of country development. Efforts have been made through establishing opportunities for education programs both local and overseas. For that purpose, Universiti Putra Malaysia (UPM) is one of the choices especially for higher education. Being far away from home, students from Indonesia may find many challenges in pursuing their study. Hence, they need to adapt well with their new environment in Malaysia. A study was carried out to investigate factors influencing postgraduate students from Indonesia to adapt with academic and socio-culture in UPM Malaysia.Survey methodology research was used for the study and the data were collected through 94 questionnaires distributed to Master and Doctoral Indonesians students from different areas of study in UPM. The data were then analyzed using Statistical Package for the Social Sciences (SPSS). Results indicated that 62.80% of the respondents were males and the rest were females with the average age of 33 years. Most of the students (53.20%) came from Sumatra and the rest from Java. The individual and environment factors strongly influenced them at means of 3.96 and 3.18 with standard of deviations at 0.80 and 0.92, respectively. Social factor was in a lower level at a mean of 3.18 and a standard of deviation at 0.92. It was found that their level of academic adaptation was good with a mean of 3.93 and a standard deviation of 0.68, but that of socio-culture was in medium level with a mean of 3.64 with a standard deviation of 0.75. There was a significant and positive relationship between individual, social and environmental factors with academic and socio-culture adaptation at p <0.05. The coefficient correlation (r) for academic adaptation was 0.36 (middle) for individual, 0.10 (weak) for social, 0.53 (strong) for environment, while for socio-culture adaptation was 0.30 (middle) for individual, 0.20 (weak) for social and 0.40 (middle) for environment.Result of stepwise regression analysis indicates that the effect of environmental factor was very dominant to academic adaptation (36%) and socio-culture (16%). It followed by individual factor that has strong effect to academic adaptation (33%). However, the effect of social factor was not significant to academic adaptation and socio-culture. To obtain a speedy adaptation in academic and socio-culture for Indonesian students as well as the other foreign students, it is suggested the students be well prepared in aspects, such as physical, mental, English fluency, budget and moral support from their family. It is also suggested that the university establishes programs for foreign students to adapt quickly with their new environment, such as orientation program for introducing campus life and Malaysian socio-culture, good services for all students, and safety guaranty for students’ life in campus. It is hoped that these program will have a good impact not only for the students but also for the university.